2020
DOI: 10.1101/2020.08.23.263665
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolution and antiviral activity of a human protein of retroviral origin

Abstract: SummaryViruses circulating in wild and domestic animals pose a constant threat to human health1. Identifying human genetic factors that protect against zoonotic infections is a health priority. The RD-114 and Type-D retrovirus (RDR) interference group includes infectious viruses that circulate in domestic cats and various Old World monkeys (OWM), and utilize ASCT2 as a common target cell receptor2. While human ASCT2 can mediate RDR infection in cell culture, it is unknown whether humans and other hominoids enc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 107 publications
(155 reference statements)
0
7
0
Order By: Relevance
“…For instance, Syncytin-1 , a human-endogenous retrovirus (HERV) gene with a clear role in human placental formation (31, 32), has also been associated with the development of neuropsychological disorders and multiple sclerosis under certain environmental stress conditions such as infection, or drug application (29, 33). Similarly, Supressyn , another gene from a retroviral origin also involved in placental development, has been recently linked with resistance to viral infection, demonstrating that its effect is context-dependent (30). Our results thus showed that besides TE-induced coding mutations, the effect of TE-induced regulatory mutations is also complex, and further suggest that TEs could be more likely to have complex effects compared to SNPs (10, 34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Syncytin-1 , a human-endogenous retrovirus (HERV) gene with a clear role in human placental formation (31, 32), has also been associated with the development of neuropsychological disorders and multiple sclerosis under certain environmental stress conditions such as infection, or drug application (29, 33). Similarly, Supressyn , another gene from a retroviral origin also involved in placental development, has been recently linked with resistance to viral infection, demonstrating that its effect is context-dependent (30). Our results thus showed that besides TE-induced coding mutations, the effect of TE-induced regulatory mutations is also complex, and further suggest that TEs could be more likely to have complex effects compared to SNPs (10, 34).…”
Section: Discussionmentioning
confidence: 99%
“…3 and 4). Previous evidence for the complex effects of TE-induced mutations were mostly associated with coding mutations (29, 30). For instance, Syncytin-1 , a human-endogenous retrovirus (HERV) gene with a clear role in human placental formation (31, 32), has also been associated with the development of neuropsychological disorders and multiple sclerosis under certain environmental stress conditions such as infection, or drug application (29, 33).…”
Section: Discussionmentioning
confidence: 99%
“…Other viral sensors activated by endo retroviral transcripts include RIG-1, MDA, TLR3, and TLR9 which all trigger the activation of interferon stimulating genes and antiviral immunity [ 91 ]. Furthermore, Endo-retroviral envelope [ 92 , 93 ] and gag proteins [ 94 , 95 ] are linked with the interference of both viral entry and replication. The outcomes of these studies are quite remarkable as it illustrates the effect of some protective responses that could be obtained from endo-retroviral reactivation by the bacteriome.…”
Section: Crosstalk Between the Virome And The Bacteriome In The Intes...mentioning
confidence: 99%
“…This inhibitory effect was associated with decreased surface levels of the virus entry receptor monocarboxylate transporter-1 (MCT-1). Similarly, the Envderived protein Suppressyn may protect humans and other hominoids from retroviral infections as it blocks the surface receptor ASCT2 that mediates attachment of RD114/mammalian type-D retroviruses (57). Members of this virus group circulate in nonhuman primates and other mammalian species.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Our knowledge about endogenous retroviral elements involved in cellular immune responses is constantly increasing. Recent key findings include the discovery of retroviral Envs restricting retroviral infection in primates (56,57), the identification of a SUMO-dependent pathway of antiviral immunity that involves sensing of ERV nucleic acids (15), as well as the description of additional retroviral promoter and enhancer elements regulating antiviral gene expression (93,97,107). These reports not only provide important insights into innate antiviral defense mechanisms, but also help to assess the role of ERV activation that is observed in a variety of infectious and non-infectious diseases.…”
Section: Importance and Future Directionsmentioning
confidence: 99%